Donner l’alerte à bas bruit : Pour une éthique des soins agroécologiques au Chili - Biskupovic, Consuelo; Maurines, Béatrice; Antin, Mélanie (Anthropologica, 2025)
Communities and individuals have raised the alarm for decades denouncing the Chilean development model and the resulting social- environmental degradation of the country. This article addresses how small manual actions are multiplying in various regions of Chile to respond to the environmental crisis, in a context marked by the production of extractive industries (production of salmon, pine trees, eucalyptus, fruit for export, copper, lithium). This article aims to underscore the development of agroecological projects or those transitioning to agroecology in the south of Chile, in Chiloé and in the regions of Araucanía, historically Mapuche territory. Their practices contribute to promoting and transmitting ancestral knowledge and expertise related to seed-saving, family and peasant farming, co-operation and the organization of territorial defence collectives. Our work is based on a method uniting long-term investigation and patchwork ethnography, based on short but in-depth research stays. Interviews complement the data. Lastly, this work contributes to considering an ethics of care across agroecological projects led by women in the south of Chile.